Split crest technique for implant treatment of agenesis of the upper lateral incisors: results of a randomized pilot histological and clinical study at 24-month follow-up - Giovanna IEZZI; Vittoria PERROTTI; Adriano PIATTELLI; Camillo D'ARCANGELO; Federica ALTIERI; Michele CASSETTA
Abstract Agenesis of lateral incisors, besides the functional issues, represents a great esthetic drawback. The selection of an appropriate treatment is a complex decision, which should consider the stability of the clinical outcomes over time. The aim of the present study was a histological and clinical comparison of two-stage split crest technique (SCT), with bone chips alone or mixed with porcine bone in patients affected by unilateral and bilateral agenesis of the upper lateral incisors. Eleven patients were enrolled, and randomly assigned to receive a treatment with autologous bone chips (group 1) or autologous bone chips mixed 1:1 to porcine-derived xenogenic bone (group 2). After a 2-month healing period, implants were placed and biopsies harvested for histomorphometrical evaluation. Clinical assessment, according to ICOI PISA health scale, and radiographic marginal bone loss evaluation at 12- and 24-month follow-ups were conducted. The histomorphometry showed significantly greater new bone formation (p > 0.0229) in group 2. At 12- and 24-month follow-ups, all the evaluated implants, regardless of the group they were allocated, could be categorized as "success" in the ICOI Pisa Health Scale for Dental Implants, and did not show significant difference in crestal bone loss. To the best of our knowledge, these are the first histological and clinical outcomes indicating that the use of bone chips mixed 1:1 to porcine bone in SCT could be a promising technique for the rehabilitation of patients with agenesis of the upper lateral incisors, although studies with a larger number of patients and implants, and a longer follow up are needed.